Participative methodological approaches and agroecology in the national police of technique assistance and agricultural extension (Revista de Ciências Agroveterinárias, 2008)
The new phase of the Brazilian Assistance Technique and Agricultural Extension Service – ATER, initiated in 2003, has as major principles the adoption of participative methodologies and the technological paradigm based on the agroecology. Those principles are based on the valuation of native knowledge, also called as traditional or local knowledge. This paper intends to discuss the changes in ATER Public Polices in Brazil, bringing theoretical and conceptual elements that help to install a new service with solid bases towards the success of this new extension phase. The idea of traditional or native agriculturist is questioned, since it can be relative. How to include the familiar agriculturist, who bases his production in the conventional technology, in that new phase, is also discussed. The paper concludes pointing out two possibilities: relative native and the reflections of Giddens about reflexive modernity.
Keywords: native; reflexive modernity; agricultural extension; agroecology.